Reconsideration of the gallium nitride: Dual functionality as an electron transporter and transparent conductor for recyclable polymer solar cell substrate applications - Lee, Kwang Jae; Yoon, Sang Eun; Jeon, Gyeong G.; Jung, Sung Hoon; Jung, Tae Hoon; Cho, Namchul; Yun, Jae Sung; Kim, Jincheol; Ho-Baillie, Anita W.Y.; Baek, Jong Hyeob; Song, Myungkwan; Kim, Jong H. (Solar Energy Materials and Solar Cells, 2019)
Herein, we report the dual functionality of a single n-type gallium nitride (n-GaN) layer as an electron transporter and transparent conductor, which has applications in reusable organic solar cells. After silicon doping with an optimized electron concentration, thin-film layer of GaN showed exceptional electrical properties including charge carrier mobility of 161 cm2 V−1s−1, electrical conductivity of 1.4ⅹ106 S cm−1, and sheet resistance of 11.1 Ω cm−2. Organic solar cells based on n-GaN exhibited power conversion efficiency comparable to those based on a conventional ITO/ZnO bilayered cathode. Furthermore, the n-GaN substrates exhibited reusability; due to excellent chemical stability of n-GaN, the reconstructed organic solar cells maintained their initial performance after the substrates were recycled. We suggest a new type of reusable n-GaN cathode layer featuring an integrated electron transporting layer and transparent electrode.
Keywords: Charge transport layer; Electrical conductivity; Electron concentration; Electron transporter; Electron transporting layer; Power conversion efficiencies; Solar cell substrates; Transparent conductors; Charge transport layer; Doping; Gallium nitride; Recyclable substrate; Transparent electrode